2022
DOI: 10.3390/cancers14215401
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Gut Microbiome in Predicting the Efficacy of Immunotherapy in Non-Small Cell Lung Cancer

Abstract: We performed various analyses on the taxonomic and functional features of the gut microbiome from NSCLC patients treated with immunotherapy to establish a model that may predict whether a patient will benefit from immunotherapy. We collected 65 published whole metagenome shotgun sequencing samples along with 14 samples from our previous study. We systematically studied the taxonomical characteristics of the dataset and used both the random forest (RF) and the multilayer perceptron (MLP) neural network models t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 64 publications
(82 reference statements)
2
7
0
Order By: Relevance
“…In a non-small cell lung cancer cohort, gut microbiota composition by functional rather than taxonomic classification successfully predicted responses to IO, and it is interesting to note that, the model suggested that interactive metabolic processes were regulating the response. 28 These findings were supported by previous studies that demonstrated the importance of amino acids, folate, and VitB12 in the activity of cytotoxic T cells. Meanwhile, in mouse models, probiotics were associated with impaired responses to checkpoint inhibitors and larger tumors.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…In a non-small cell lung cancer cohort, gut microbiota composition by functional rather than taxonomic classification successfully predicted responses to IO, and it is interesting to note that, the model suggested that interactive metabolic processes were regulating the response. 28 These findings were supported by previous studies that demonstrated the importance of amino acids, folate, and VitB12 in the activity of cytotoxic T cells. Meanwhile, in mouse models, probiotics were associated with impaired responses to checkpoint inhibitors and larger tumors.…”
Section: Discussionsupporting
confidence: 74%
“…The intricate balance of gut microbiota, in turn, has been shown to affect host immune responses, in an immune-metabolic interplay. In a non–small cell lung cancer cohort, gut microbiota composition by functional rather than taxonomic classification successfully predicted responses to IO, and it is interesting to note that, the model suggested that interactive metabolic processes were regulating the response 28 . These findings were supported by previous studies that demonstrated the importance of amino acids, folate, and VitB12 in the activity of cytotoxic T cells.…”
Section: Discussionsupporting
confidence: 67%
“…Immune regulation-related gene profiles in patient biopsy samples were analyzed by Wiesweg et al . [ 52 ] to develop an ML model to predict the impact of genomic information and TME on the therapeutic response for IV NSCLC.…”
Section: The Applications Of Ai and ML In Lung Cancer Immunotherapy P...mentioning
confidence: 99%
“…In fact, in mouse models, disruption of the gut microbiome impacted the response of tumors to immunotherapy [ 65 ]. Studies in humans have also found an association between certain bacterial species within the microbiome and the patient’s response to immunotherapy [ 24 , 25 , 66 ]. Intestinal microbiota have previously been implicated in the modulation of cancer immunotherapy [ 65 ] and chemotherapy [ 67 ].…”
Section: Microbiome-time Axis In Tumorigenesis and Cancer Treatmentmentioning
confidence: 99%
“…As previously discussed, different species within the microbiome confer beneficial immunomodulation while other species result in a cancer-promoting environment. Because of the microbiome-TIME axis, it has been proposed that the microbiome could be used as a clinical predictor of disease course and to predict the likelihood of response and adverse events related to immunotherapy treatment [ 14 , 66 ]. It is imperative that further work is conducted to identify optimal combinations of bacteria so as to optimize the antitumor response and minimize adverse events.…”
Section: Clinical Implications and Future Directions Of Microbiome-ti...mentioning
confidence: 99%